The utility of apparent diffusion coefficients for predicting treatment response to uterine arterial embolization for uterine leiomyomas: a systematic review and meta-analysis - Dyda Dao; Sally J. Kang; Mehran Midia (Diagnostic and Interventional Radiology, 2019)

(untitled)
PURPOSEApparent diffusion coefficient (ADC) values, which are derived from diffusion-weighted imaging, have a potential role for predicting treatment response. A systematic review was conducted to examine the value of baseline ADC values for predicting leiomyoma size reduction after uterine arterial embolization (UAE).METHODSStudy selection, quality appraisal and data extraction were conducted independently by two authors. Statistical analyses included the calculation of weighted means and summary correlation coefficients (under the random effects model).RESULTSEleven studies consisting of a total of 258 patients (age, weighted mean±standard deviation [SD], 43.1±10.1 years) were included. The weighted mean±SD ADC value was 1.2±1.5 ×10-3 s/mm2 at baseline (ten studies) and 1.3±2.8 ×10-3 s/mm2 at approximately 6 months after embolization (six studies). The weighted mean percentage leiomyoma volume reduction (VR) at 6 months was 47.1%±35.6% (seven studies). Based on four studies, the weighted summary correlation coefficient for the correlation between baseline ADC and leiomyoma VR at approximately 6 months was not significant (r=0.40; 95% CI, -0.07 to 0.72; I2=69.7%). No associations were found in three of the four studies that examined changes in ADC values as a predictor.CONCLUSIONDue to high heterogeneity, it is unclear whether ADC may be useful for predicting treatment responses to UAE.